The rise of ICTs in the Pacific - Mangal, Anju; Berrell, Jacqui (Technical Centre for Agricultural and Rural Cooperation, 2013)
A Pacific-wide online discussion looked at the use of mobile phones and how fast-improving internet access will bring about change in the region.